Attack-tempo and attack-type as predictors of attack point from opposite players in volleyball - Marcelino, R.; Mesquita, I.; Cesar, B. (World Congress of Performance Analysis of Sport VIII, 2008)
The results show that it is more likely to make point in fast attack situations (tempo 1) with combination. This trend is the same in relation to making error or allowing the continuity of the game. Indeed, the relationship between point - error and point - continuity loses strength as the attack is slower and without combination. These results are particularly important since nowadays the high level game is characterized by an increase in game speed on the sides of the net supported by offensive pattern combinations (Marcelino & Mesquita, 2006a; Marelic et al., 1998). Therefore in the long term it should be a priority to integrate these characteristics, gradually, into the training of young players.